2013
DOI: 10.11607/jop.943
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Temporomandibular Disorders Are Not Necessarily Associated with a Compromised Endogenous Analgesic System

Abstract: Aims Our previous work demonstrated that women with temporomandibular disorder (TMD) exhibit enhanced temporal summation of pain upon repetitive mechanical stimulation of the fingers, compared to healthy controls, suggestive of widespread up regulated central nociceptive processing in this patient population. The current study asks whether TMD case-control differences in Conditioned Pain Modulation (CPM) exist, using a mechanically evoked Temporal Summation (TS) model. Methods A series of 10 repetitive, mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 33 publications
4
33
0
Order By: Relevance
“…The study search strategy is presented in the form of a flow chart (Figure ). Twenty‐two articles (11 case‐control studies and 11 cross‐sectional studies) met the inclusion criteria, of which 8 were included in the meta‐analysis (5 cross‐sectional and 3 case‐control studies). Descriptive characteristics of the studies included in this study are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study search strategy is presented in the form of a flow chart (Figure ). Twenty‐two articles (11 case‐control studies and 11 cross‐sectional studies) met the inclusion criteria, of which 8 were included in the meta‐analysis (5 cross‐sectional and 3 case‐control studies). Descriptive characteristics of the studies included in this study are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…All patients in the studies had experienced pain in the TMJ area for at least 3 months. As for the pain characteristics in the experimental group #bib11 studies included data about myofascial pain, 4 of the studies included mixed pain (myogenous and arthrogenous), and 1 study referred only to arthrogenous pain . In addition #bib4 studies referred to nonspecific orofacial pain, and 2 studies did not describe the characteristics of pain .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temporomandibular disorder has also been explored in this regard. King et al 37 reported less efficient CPM in these patients; Garrett et al 24 reported CPM similar to healthy controls, whereas Kothari et al 42 reported reduced CPM in TMDs after surgery. Oono et al 69 reported reduced CPM in TMD, but only when measured from affected sites.…”
Section: Idiopathic Pain Syndromesmentioning
confidence: 95%
“…This finding is in agreement with a study by Staud et al 59 on patients with chronic widespread pain, but in contrast to a previous study that showed reduced TS during the cold pressor test in patients with temporomandibular disorder. 60 Different pain conditions, assessment time points, and assessment sites may explain the equivocal results. Moreover, in healthy participants, paradigms of CPM have been shown to reduce temporal summation of pain, 61 highlighting potential differences in the effect of the CPT on central pain mechanisms of pain summation between healthy participants and patients with chronic pain.…”
Section: Cpmmentioning
confidence: 99%